STRATEGI PERTUMBUHAN BERKELANJUTAN INDOFOOD DI PASAR KOMPETITIF - Mubarok, Muhammad Husni (BISNIS, 2014)
This study aims to analyze the strategy of continuous growth for sustainability PT. Indofood Sukses Makmur, Tbk in competitive market. The scope of this study include corporate strategy, business competition, competitive advantage, business portfolio, marketing and international strategy. The results showed that Indofood using a strategy of diversified product portfolio, which capitalizes on a resilient business model with five complementary strategic business groups, namely: consumer branded products, bogasari, agribusiness, distribution, cultivation & processed vegetables. Consumer products group has six divisions namely: noodles, dairy, snack foods, food seasonings, nutrition & special foods, and beverages division. While the agribusiness group has a plantations and edible oils and fats division. Competitive strategy business using more products to offer through innovation. International strategy of using licenses and joint ventures.